1995
DOI: 10.2307/3588167
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Ethnicity as Factors in the Development of Verbal Skills in Bilingual Mexican American Women

Abstract: This study describes and analyzes differences in student output across ethnicity and gender in a mixed monolingual English and bilingual Spanish/English class in order to understand how L2 oral language skills are developed in a mixed classroom. Primary participants in the study included approximately 30 basic writing students ranging in age from 18 to 60. Fifty-five percent of the students were bilingual Mexican American, and the remainder were monolingual Anglo Americans. Participant observation, informal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…It includes those 'actions, behaviours, steps or techniques students use, often unconsciously, to improve their progress in apprehending, internalising, and using the L2' (Oxford 1990, 1). There is a growing recognition that language learning is a more complex process than merely acquiring linguistic structures, and that language learning and use are shaped by sociocultural processes (Hall 1995;Losey 1995;McKay and Wong 1996;Zuengler 1989). Central to these language learning strategies are all of the surrounding sociocultural processes such as racial or ethnic sensibility occurring through everyday life (Thomas and Collier 1997).…”
Section: Social Context Language Motivation and Strategymentioning
confidence: 98%
“…It includes those 'actions, behaviours, steps or techniques students use, often unconsciously, to improve their progress in apprehending, internalising, and using the L2' (Oxford 1990, 1). There is a growing recognition that language learning is a more complex process than merely acquiring linguistic structures, and that language learning and use are shaped by sociocultural processes (Hall 1995;Losey 1995;McKay and Wong 1996;Zuengler 1989). Central to these language learning strategies are all of the surrounding sociocultural processes such as racial or ethnic sensibility occurring through everyday life (Thomas and Collier 1997).…”
Section: Social Context Language Motivation and Strategymentioning
confidence: 98%
“…Moreover, as demonstrated by Heller (1999) and Losey (1995), even when immigrant and minority women do access the classroom, they may get significantly less classroom interaction time than either minority men or majority men and women. Losey's (1995) study of classroom participation patterns of American and Mexican-American students in a community college classroom persuasively demonstrated that Mexican-American women were doubly marginalized in the class, both as ethnic minority members and as women, and thus prevented from taking their turns, expressing themselves, and interacting in the target language.…”
Section: Gendered Access To Linguistic Resources In Multilingual Contmentioning
confidence: 91%
“…Losey's (1995) study of classroom participation patterns of American and Mexican-American students in a community college classroom persuasively demonstrated that Mexican-American women were doubly marginalized in the class, both as ethnic minority members and as women, and thus prevented from taking their turns, expressing themselves, and interacting in the target language. Similarly, Heller (1999) shows that older immigrant girls are the ones who are alienated most in a French-language high school in Toronto, Ontario, and have least access to its linguistic resources, in particular, English.…”
Section: Gendered Access To Linguistic Resources In Multilingual Contmentioning
confidence: 98%
See 1 more Smart Citation
“…A significant number of scholars highlight the importance of individual learners, their motivation, and sociocultural context (Brown 2000(Brown , 2001Cummins 1988;O'Malley and Chamot 1990;Oxford 1990;Thomas and Collier 1997). The rise of sociolinguistic and contextual approaches in second language research over the past decade reflects a growing recognition that learning language is a more complex process than merely acquiring linguistic structures, and that language learning and use are shaped by sociocultural process (Hall 1995;Losey 1995;McKay and Wong 1996;Zuengler 1989). According to the Prism Model produced by Thomas and Collier (1997), central to that student's acquisition of language are all of the surrounding sociocultural processes such as racial or ethnical sensibility occurring through everyday life.…”
Section: Motivations and Strategies Of Second Language Learningmentioning
confidence: 98%